Morphology and Bioethanol Potential of Amorphophallus muelleri Blume Variants Found in East Java - Priyanti, Novie Ary; Habiburrahman, Novan (At- Ta'lim : Jurnal Pendidikan, 2024)
Amorphophallus muelleri Blume (porang) is a high-economic value plant widely found in Indonesia, particularly in East Java. The morphological variations of this plant play a significant role in selecting superior seeds and adapting to environmental conditions. Additionally, porang has potential in the energy sector, particularly in biomass energy conversion from its tubers, which are rich in glucomannan. This study aims to analyze the morphological differences of A. muelleri from various regions in East Java and its potential for biomass energy utilization. The observed parameters include the pattern and color of petioles, the shape and color of tubers, and glucomannan content as the main indicator of energy potential. The results indicated three main groups based on petiole patterns: (1) large prismatic, (2) small prismatic, and (3) striped prismatic. The tuber morphology also showed significant differences in shape, color, and water content, which affect energy conversion efficiency. Higher glucomannan content in certain variants suggests their potential as raw materials for bioethanol or renewable energy biomaterials. This emphasizes that morphological variation is not only crucial for selecting superior seeds but also for optimizing energy utilization from porang tubers.